2013
DOI: 10.1302/0301-620x.95b12.31918
|View full text |Cite
|
Sign up to set email alerts
|

Simple debridement has little useful value on the clinical course of recalcitrant ulnar wrist pain

Abstract: The purpose of this study was to evaluate treatment results following arthroscopic triangular fibrocartilage complex (TFCC) debridement for recalcitrant ulnar wrist pain. According to the treatment algorithm, 66 patients (36 men and 30 women with a mean age of 38.1 years (15 to 67)) with recalcitrant ulnar wrist pain were allocated to undergo ulnar shortening osteotomy (USO; n = 24), arthroscopic TFCC repair (n = 15), arthroscopic TFCC debridement (n = 14) or prolonged conservative treatment (n = 13). The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 25 publications
0
38
0
1
Order By: Relevance
“…13,15 (Table 3) The pre-operative radioulnar deviation was 43° (ones study). 13 The mean post-operative extension/flexion arc was 146° ± 18° with a range of 117°–163°, 7,12,13,15,22,25 the mean post-operative pronosupination arc was 161° ± 11° with a range of 152°–178° 7,12,13,15,22 , and the mean post-operative radioulnar deviation arc was 53° ± 5° with a range of 46°–58°. 7,12,13,19,22 These radioulnar deviation data are inclusive of all studies that presented post-operative arc of motion.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…13,15 (Table 3) The pre-operative radioulnar deviation was 43° (ones study). 13 The mean post-operative extension/flexion arc was 146° ± 18° with a range of 117°–163°, 7,12,13,15,22,25 the mean post-operative pronosupination arc was 161° ± 11° with a range of 152°–178° 7,12,13,15,22 , and the mean post-operative radioulnar deviation arc was 53° ± 5° with a range of 46°–58°. 7,12,13,19,22 These radioulnar deviation data are inclusive of all studies that presented post-operative arc of motion.…”
Section: Resultsmentioning
confidence: 98%
“…The mean pre-operative extension/flexion arc was 120° ± 3° with a range of 118°–122° 13,15 and the mean pre-operative pronosupination arc was 140° ± 14° with a range of 132°–152°. 13,15 (Table 3) The pre-operative radioulnar deviation was 43° (ones study).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 In addition, previous studies have reported that conservative treatment or arthroscopic debridement for damaged TFCC provided unsatisfactory clinical outcomes, or resulted in persistent symptoms, in more than half of the cases. 30,31 In contrast, a long-term follow-up study after conservative treatment for distal radius fracture reported that TFCC injury did not affect the final outcome. 32 Therefore, it appears that no study has accurately identified the recovery period that is needed to resolve a TFCC injury that caused DRUJ instability.…”
Section: Table 5 Three-month Follow-up Outcomesmentioning
confidence: 99%